Economic Growth, Demographic Change and Rural-Urban Migration in China - Fu-ning ZHONG; Qing LI; Jing XIANG; Jing ZHU (Journal of Integrative Agriculture, 2013)
Is China able to maintain fast growth after three decades? This paper tries to answer this question by: 1) arguing that factors contributed to sustained long-run growth at supply side; 2) focusing on contributions of demographic dividend especially that of rural-urban migration; and 3) analyzing rural demographic change with information collected through village-wide household survey. Policy alternatives to realize remaining potential demographic dividend are proposed based on the analysis of changing rural demographic structure.